Government's Role in TPA Waste Management: Peran Pemerintah dalam Pengelolaan Limbah di TPA - Alfi, Lisa Dwi; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the government's role in waste management at Jabon TPA, Jabon District, Sidoarjo. Employing a descriptive qualitative approach, data collection involves interviews, observation, and documentation, utilizing purposive sampling. The analysis encompasses data collection, reduction, analysis, and conclusion drawing. The findings reveal effective and smooth execution of the government's role in waste management, as evidenced by the fulfillment of various indicators. The study's concise yet comprehensive nature provides valuable insights into the successful governance of waste management practices, offering implications for broader contexts and policy considerations Highlight : The study employs a qualitative approach to investigate the government's role in waste management at Jabon TPA, providing valuable insights into the effectiveness of governance practices. Data collection through interviews, observation, and documentation, utilizing purposive sampling, ensures a comprehensive and thorough examination of the waste management scenario. The findings demonstrate the successful fulfillment of government roles, marking a significant contribution to the discourse on efficient waste management practices and policy considerations Keywords: Waste Management, Government Role, Descriptive Research, Qualitative Approach, Jabon TPA